Forrest Gump : the novel - Groom, Winston, 1944- (New York : Pocket Books, 1986)
Through three turbulent decades, Forrest rides a tide of events that whisks him from physical disability to football stardom, from Vietnam hero to shrimp tycoon, from White House honors to the arms of his one true love.
New York Times.
Publisher's Weekly.
Adult
Keywords: People with mental disabilities -- Fiction; Young men -- United States -- Fiction; Humorous fiction; Mentally handicapped -- Fiction; Young men -- Fiction; Humorous stories